Capillary Discharge XUV Radiation Source - M. Nevrkla (Acta Polytechnica, 2009)
A device producing Z-pinching plasma as a source of XUV radiation is described. Here a ceramic capacitor bank pulse-charged up to 100 kV is discharged through a pre-ionized gas-filled ceramic tube 3.2 mm in diameter and 21 cm in length. The discharge current has amplitude of 20 kA and a rise-time of 65 ns. The apparatus will serve as experimental device for studying of capillary discharge plasma, for testing X-ray optics elements and for investigating the interaction of water-window radiation with biological samples. After optimization it will be able to produce 46.9 nm laser radiation with collision pumped Ne-like argon ions active medium.